Reuse of water in the irrigation of papaya seedlings in the Brazilian semiarid - Bezerra, Diego Ernani Leite (2019)
Irregular pluvimetric precipitations and high evapotranspiration are characteristic of the semiarid region of northeastern Brazil. The set of these variables make water a limiting factor for irrigated agriculture, which makes reuse necessary, especially in places under conditions of growing scarcity. The objective of this work was to propose the use of water from air conditioning and agroindustrial effluent in the production and development of papaya seedlings. The research was developed in the seedling production sector located at the Federal Institute of Paraíba, Campus Sousa. A completely randomized block design was used, with five treatments and four replications. The treatments were the use of water from artesian well, air conditioning of the combination air conditioning and artesian well (1:1), of agroindustrial effluent; Of the combination of agroindustrial effluent and air conditioning (1:1). Papaya seedlings were produced in plastic bags, using Neossol Fluvic and manure in proportion (2:1) as substrate. The following variables were evaluated: plant height, stem diameter, number of leaves, green and dry mass of shoots and roots, content of (nitrogen, phosphorus and potassium) of leaves and influence on soil attributes (PH, P, K, Na, Ca, Mg, MO, PST). The use of water from agroindustrial effluent infered lower results for most variables. The use of air-conditioning waters emerges as an economically viable alternative for the use in irrigation of papaya seedlings.